Increasing the Potential of Concessions to Expand Rural Electrification in Sub-Saharan Africa - Hosier, Richard (World Bank, Washington, DC, 2017)
The record of concession arrangements in stimulating faster and more effective rural electrification in Sub-Saharan Africa is mixed at best: More concessions have failed than have been implemented—and among concessions that have been implemented, none can be considered an unequivocal success. Still, properly structured agreements can expand electrification by connecting more households to the national grid or to mini-grids. Lessons from case studies shed light on the circumstances under which concessions work best.